Design and Motion Simulation of the Drive Mechanism of Oil-immersed Transformer Spherical Detection Robots - Zhou Jiajun; Wu Binghui; Ji Dongmei; Deng Yangtai (Jixie chuandong)
Aiming at the complex environment inside the oil-immersed transformer, a spherical detection robot is proposed according to the design requirements such as a fault detection. Taking the pendulum eccentric torque as the core, two drive mechanism schemes are proposed. Based on the advantages of Simscape parametric modeling, the Simscape physical model is established, and then the influence of different pendulum lengths on the upward and downward fluctuation amplitude and forward speed of spherical robots is analyzed by changing the radial position of the heavy hammer. At the same time, according to the simulation comparison and the bearing capacity of the instrument inside the spherical robot, the appropriate drive mechanism scheme is selected. Then, the dynamic model of the drive mechanism is constructed, and the rationality of the eccentric moment drive mechanism of the single pendulum is analyzed and verified. Finally, according to the special requirements of the structure and environment of the oil-immersed transformer, physical experiments are carried out to verify the optimization effect of the drive mechanism. The results show that in the face of different task environments, the swing length can be changed according to the demand to control the fluctuation amplitude and forward speed of the spherical robot, so that the fluctuation amplitude and forward speed of the robot are within the tolerance range of the internal instrument, and the fault detection is better carried out in the narrow area of the oil-immersed transformer, which provides a basis for the development of the experimental prototype of the spherical detection robot of the oil-immersed transformer later.